Menuju Masa Depan Akuntansi : Memanfaatkan Potensi Kecerdasan Buatan dalam Pelaporan Keuangan - Rehanindya Krispradana; Dikho Rahmat Mauluddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the potential application of artificial intelligence (AI) in financial accounting, especially in the financial reporting process. AI has the ability to improve efficiency, accuracy, and automation in financial data processing, as well as provide real-time information that supports strategic decision making. The research method used is a qualitative approach through literature studies and secondary data analysis from various relevant previous studies. The results of the study indicate that the application of AI in accounting can improve the efficiency and accuracy of the financial reporting process, while reducing human error. However, ethical and technical challenges such as data privacy and transparency in the use of AI are major concerns that must be addressed. The suggestions given in this study are the importance of improving the competence of accountants in the use of AI technology, implementing strict regulations to maintain data security and privacy, and continuous monitoring and evaluation of the use of AI in accounting. By utilizing AI optimally and responsibly, companies can gain great benefits in financial reporting while overcoming existing challenges.